Overexpression of α-acetolactate decarboxylase and acetoin reductase/2,3-butanediol dehydrogenase in Arabidopsis thaliana - Dempers, Dehan (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScAgric)--Stellenbosch University, 2015.